The Prevalence of Gastroesophageal Reflux Disease in Azerbaijan: A Population-Based Cross-sectional Study - Aghayeva, Sevda; Katzka, David; Afandiyeva, Nargiz; Bor, Serhat; Babayeva, Gulustan; Hidayatov, Alihuseyn; Mammadzada, Gulay (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The prevalence of gastroesophageal reflux disease in Azerbaijan has not been evaluated before. The aim of our study was to determine the prevalence of gastroesophageal reflux disease based on the validated reflux questionnaire. Materials and Methods: A total of 1026 individuals from 7 regions of Azerbaijan were included in the cross-sectional study conducted via face-to-face administration of the validated Mayo Clinic’s gastroesophageal reflux disease questionnaire. Gastroesophageal reflux disease was diagnosed if an individual had heartburn and/or regurgitation occurring at least once a week. Results: The prevalence of gastroesophageal reflux disease in Azerbaijan was 22.7% with significant female predominance (26.1% vs. 15.3%; P < .0001). Gastroesophageal reflux disease was prevalent in 17% of those aged below 35 years; 22.7% of those in the age range 36-55 years, and 38.5% of those who are above 56 years, which, accordingly, indicates that gastroesophageal reflux disease becomes significant as age increased (P < .0001). Male respondents younger than 35 years had much lower rates of gastroesophageal reflux disease than in older groups (5.7% vs. 22.7%, P < .0001), whereas in females older than 55 years, age was a significant factor for increasing gastroesophageal reflux disease symptoms (22.6% vs. 50%, P < .001). Reflux was observed in 18.1% of normal-weight respondents (body mass index 18.6-24.9), 25.6% of overweight (body mass index 25-29.9), and 30.4% of obese ( body mass index > 30) individuals (P = .001). Regarding marital status, the prevalence was the lowest in the single subjects’ group (17%), close to average in the married group (23.8%), and the highest (41.7%) in divorced/widowed cases (P = .003). Stress significantly affected the gastroesophageal reflux disease distribution, affecting 59.4% of all respondents (P < .004). Conclusion: Gender, body mass index, increased age, marital status, and stress were precipitating factors of gastroesophageal reflux disease. Socioeconomic diversity, along with lifestyle/habits, did not play a crucial role in the gastroesophageal reflux disease prevalence distribution.